The Mangal Play: A serious game to experience multi-stakeholder decision-making in complex mangrove social-ecological systems - Dahdouh-Guebas, Farid; Mafaziya Nijamdeen, T. W. G. F.; Hugé, Jean; Dahdouh-Guebas, Yasmin; Di Nitto, Diana; Hamza, Amina Juma; Kodikara Arachchilage, Sunanda; Koedam, Nico; Mancilla García, María; Mohamed, Mohamed O. S.; Mostert, Laurence; Munga, Cosmas N.; et al. (Frontiers in Marine Science, 2022)
In order to achieve collaborative action in nature conservation and natural resources management, stakeholders have to understand and acknowledge other stakeholders’ interests, values, world visions and objectives and they have to overcome the problem of irrational decision-making through innate opposition discourses. In this paper we developed the Mangal Play, an experiential learning method to have participants adopt the role of a particular stakeholder in an imaginary mangrove forest social-ecological system (SES). The Mangal Play is a serious game, more specifically a role-play, aimed at promoting oral dialogues between 20 stakeholders involved in governance, fisheries, aquaculture, agriculture, forestry, tourism, transport, conservation and communication sectors. By providing tools to lecturers and scientists to execute it in a public or classroom setting, the Mangal Play stimulates a decision-making process while accepting compromise and distinguishing bottom-line issues from negotiable positions, and instructs about the behaviour of complex real-world systems in a safe learning environment. We exemplify how social network analysis can serve to visualise the outcome and further develop the Mangal Play. In this way we hope to help stakeholders take into account diverse positions in a rational decision-making process.